Cognitive Profiles and Hub Vulnerability in Parkinson's Disease - Lin, Sue-Jin; Baumeister, Tobias R.; Garg, Saurabh; McKeown, Martin J. (Frontiers in Neurology, 2018)
The clinicopathological correlations between aspects of cognition, disease severity and imaging in Parkinson’s Disease (PD) have been unclear. We studied cognitive profiles, demographics and functional connectivity patterns derived from resting-state fMRI data (rsFC) in 31 PD subjects from the Parkinson’s Progression Markers Initiative (PPMI) database. We also examined rsFC from 19 healthy subjects (HS) from the Pacific Parkinson’s Research Centre. Graph theoretical measures were used to summarize the rsFC patterns. Canonical correlation analysis (CCA) was used to relate separate cognitive profiles in PD that were associated with disease severity and demographic measures as well as rsFC network measures. The CCA model relating cognition to demographics suggested female gender and education supported cognitive function in PD, age and depression scores were anti-correlated with overall cognition, and UPDRS had little influence on cognition. Alone, rsFC global network measures did not significantly differ between PD and controls, yet some nodal network measures, such as network segregation, were distinguishable between PD and HS in cortical “hub” regions. The CCA model relating cognition to rsFC global network values, which was not related to the other CCA model relating cognition to demographic information, suggested modularity, rich club coefficient, and transitivity was also broadly related to cognition in PD. Our results suggest that education, aging, comorbidity, and gender impact cognition more than overall disease severity in PD. Cortical “hub” regions are vulnerable in PD, and impairments of processing speed, attention, scanning abilities, and executive skills are related to enhanced functional segregation seen in PD. Our results suggest that education, aging, comorbidity, and gender impact cognition more than disease severity in PD. Cortical “Hub” regions are vulnerable in PD, and impairments of processing speed, attention, and scanning abilities in PD are related to enhanced functional segregation in PD.